Use of Preputial Skin as Cutaneous Graft after Nevus Excision - A. D'Alessio; E. Piro; M. Brugnoni; L. Abati (Hindawi Limited, 2010)
We report a four-year-old boy with a nevus covering all the plantar side of his second finger on the left foot. He was also affected by congenital phimosis. Surgical excision of the nevus was indicated, but the skin defect would have been too large to be directly closed. The foreskin was taken as a full-thickness skin graft to cover the cutaneous defect of the finger. The graft intake was favourable and provided a functional repair with good aesthetic characteristic.